MRI in donor candidates for living donor liver transplant: Technical and practical considerations. Issue 6 (14th October 2018) - Kim, Bohyun; Kim, So Yeon; Kim, Kyoung Won; Jang, Hye Young; Jang, Jong Keon; Song, Gi Won; Lee, Sung Gyu
Abstract : In living donor liver transplantation (LDLT), a thorough preoperative evaluation of the donor is imperative to minimize the risk of the donors and improve the outcome of the recipients. In order to select the best candidate, knowledge of the liver volume, degree of steatosis, and anatomic variations in the vascular and biliary system in potential donors is crucial. With recent technical advances, magnetic resonance imaging (MRI) is increasingly replacing the need for computed tomography (CT) examination in essential steps of donor evaluation. Along with the introduction of higher gradient strength, novel pulse sequences, and innovative contrast media, MRI has a potential to serve as an "all‐in‐one" imaging package. In this review, we provide an overview of clinical and radiologic considerations related to LDLT and highlight the basics and up‐to‐date knowledge of MRI techniques for a comprehensive donor evaluation. Level of Evidence: 5 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2018;48:1453–1467